BMP signaling mediated by constitutively active Activin type 1 receptor (ACVR1) results in ectopic bone formation localized to distal extremity joints - Agarwal, Shailesh (Dev Biol, 2015)
BMP signaling mediated by ACVR1 plays a critical role for development of multiple structures including the cardiovascular and skeletal systems. While deficient ACVR1 signaling impairs normal embryonic development, hyperactive ACVR1 function (R206H in humans and Q207D mutation in mice, ca-ACVR1) results in formation of heterotopic ossification (HO). We developed a mouse line, which conditionally expresses ca-ACVR1 with Nfatc1-Cre(+) transgene. Mutant mice developed ectopic cartilage and bone at the distal joints of the extremities including the interphalangeal joints and hind limb ankles as early as P4 in the absence of trauma or exogenous bone morphogenetic protein (BMP) administration. Micro-CT showed that even at later time points (up to P40), cartilage and bone development persisted at the affected joints most prominently in the ankle. Interestingly, this phenotype was not present in areas of bone outside of the joints – tibia are normal in mutants and littermate controls away from the ankle. These findings demonstrate that this model may allow for further studies of heterotopic ossification, which does not require the use of stem cells, direct trauma or activation with exogenous Cre gene administration.